Analysis of Tree Health in the Pematangsiantar Animal Park, North Sumatra Province - Rozalina, Rozalina; Nurrachmania, Meylida; Pangaribuan, Ryandi Goklas (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
This study aims to determineÂ acquire data on the species composition and structure of trees, as well as to analyze the health of trees growing in the Pematangsiantar Animal Park. Using the census approach, data collection was conducted. The health state of trees was determined using the Forest Health Monitoring (FHM) method, which measures tree health by categorizing the kind and severity of damage per every plant. Two indicators are utilized to measure tree health: tree damage and tree crown condition. The method of data collection was conducted on trees with a minimum diameter of 20 centimeters. Techniques of data analysis consisting of descriptive and weighted scoring. At the Pematangsiantar Animal Park, there are 49 species of trees and a total of 153 unique trees. Mahogany (Swietenia mahagoni) is the most prevalent tree species, with 21 specimens. The health state of the trees in the Pematangsiantar Animal Park included 48 trees with a healthy status, 93 trees with bad (unhealthy) status, and 12 trees with a sick status, however none were discovered to be in a very sick condition